Investigating the role of whole-school input on children's knowledge and selection of healthy foods. - Robinson, Ciara (My University, 2018)
In today's society, there is an increased emphasis on the importance of maintaining a balanced, nutritious diet. With this in mind, it should be understood that Irish primary schools should be one of the main bodies responsible for educating children about healthy eating. The aim of this research was to determine whether implementing a short term whole-school approach to healthy eating would impact on a child's knowledge and selection of food, with the awareness that if presented with a positive correlation, a long term approach to healthy eating may further heighten these positive results. The research question is answered through an experimental design that consists of both quantitative measures and action research. Over a period of five weeks, the researcher distributed two set of questionnaires to all participants, as well as conducting in-school action research. Children aged between four and eight, from Junior Infants up to 2nd class completed these questionnaires, and the whole school participated in the action research element of the design. These results indicated that a short term whole school approach to healthy eating does have an impact on children's knowledge and selection of foods. On this basis, it is recommended that Irish Primary Schools take the responsibility of educating children about healthy eating from Junior Infants all the way up to 6th class. In addition, formal healthy eating policies should be created by schools nationwide, as well as the implementation of whole school approaches which may influence children's knowledge and selection of healthy foods.
Professional Masters of Education
Keywords: Research Subject Categories; Nutrition; Diet; Healthy eating; Knowledge of Children; Formal healthy eating policies; Irish primary schools